Effects of Rotation and Inclined Magnetic Field on Walters' B Fluid in a Porous Medium using perturbation method or technique. - Jaafar, Zainab A.; Hummady, Liqaa Z.; Thawi, Mizal H. (Iraqi Journal of Science, 2024)
The peristaltic flow of Walter's B fluid through an asymmetric channel is analyzed. The constitutive equation for the balance of mass, momentum, trapped phenomena, and velocity distribution is modeled. Consideration of low Reynolds number and long wavelength assumption are used in the flow analysis to get an exact solution by using the perturbation method. The impact of impotent parameters on stream function and axial velocity has been gained. The set of figures is graphically analyzed of these parameters.